Control of Streptococcal Infections: Is a Common Vaccine Target Achievable Against Streptococcus agalactiae and Streptococcus pneumoniae - Bedeley, Edmund; Gori, Andrea; Yeboah-Manu, Dorothy; Diallo, Kanny (Frontiers in Microbiology, 2021)
Abstract Both Streptococcus agalactiae (group B streptococcus (GBS)) and Streptococcus pneumoniae (pneumococcus) remain significant pathogens as they cause life threatening infections mostly in children and the elderly. The control of diseases caused by these pathogens is dependent on antibiotics use and appropriate vaccination. The introduction of the pneumococcal conjugate vaccines (PCVs) against some serotypes has led to reduction in pneumococcal infections, however, the subsequent serotype switching, and replacement has been a serious challenge. On the other hand, no vaccine is yet licenced for use in the control of GBS diseases. In this review, we provide an overview of the history and global disease burden, disease pathophysiology and management, vaccines update and the biology of both pathogens. Furthermore, we address recent findings regarding structural similarities that could be explored for vaccine targets across both mucosal pathogens. Finally, we conclude by proposing future genomic sequence comparison using the wealth of available sequences from both species and the possibility of identifying more related structural components that could be exploited for pan-pathogen vaccine development.